1994
DOI: 10.1029/94jd00668
|View full text |Cite
|
Sign up to set email alerts
|

The Landes experiment: Biosphere‐atmosphere exchanges of ozone and aerosol particles above a pine forest

Abstract: An experiment was conducted in a pine forest in southwestern France during late spring 1992. The aim was fourfold: testing various flux measurement methodologies for chemically reactive species; quantifying the exchanges between the forest and the atmosphere; analyzing the involved mechanisms; and studying their influence on the chemistry of the surface boundary layer. This paper presents preliminary results obtained on the dry deposition of ozone and submicronic aerosol particles, measured using eddy correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 26 publications
5
45
1
1
Order By: Relevance
“…Given that there are no obvious aerosol sources to the NW, this data stratification minimizes any influence of advection. Figure 9 demonstrates the expected relationship (Lamaud et al, 1994) between deposition velocity (V dt ) and stability (as z/L) in that unstable periods display larger downward (more negative) V dt than do neutral or stable periods during EFLAT. As conditions changed from stable to unstable, the aerosol deposition velocity for 0.52 µm diameter particles increased from 0.16 to about 0.44 cm s −1 while V dt for 0.34 and 0.84 µm diameter particles increased from 0.2 to 0.6 and 0.7 cm s −1 respectively.…”
Section: Hygroscopic Growth Correction To Aerosol Deposition Velocitymentioning
confidence: 99%
“…Given that there are no obvious aerosol sources to the NW, this data stratification minimizes any influence of advection. Figure 9 demonstrates the expected relationship (Lamaud et al, 1994) between deposition velocity (V dt ) and stability (as z/L) in that unstable periods display larger downward (more negative) V dt than do neutral or stable periods during EFLAT. As conditions changed from stable to unstable, the aerosol deposition velocity for 0.52 µm diameter particles increased from 0.16 to about 0.44 cm s −1 while V dt for 0.34 and 0.84 µm diameter particles increased from 0.2 to 0.6 and 0.7 cm s −1 respectively.…”
Section: Hygroscopic Growth Correction To Aerosol Deposition Velocitymentioning
confidence: 99%
“…Size-resolved fluxes have been measured using optical particle counters (Gallagher et al, 1997;Ahlm et al, 2010), relaxed Eddy Accumulation (REA) with a Differential Mobility Particle Sizer (DMPS; Grönholm et al, 2007), and EC with a Fast Mobility Particle Sizer (FMPS; Pryor et al, 2009). Lamaud et al (1994) found that particle deposition velocity (V d ) is related to friction velocity (u * ) and atmospheric stability. This was also supported by the studies of Grönholm et al (2007), Pryor (2006), Pryor et al (2007), and Ahlm et al (2009Ahlm et al ( , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Forest types and locations include: mixed deciduous in eastern Tennessee (Hicks et al, 1989) and southern Indiana, USA (Pryor et al, 2009); pine in Hyytiälä, Finland (e.g. Buzorius et al, 1998;Grönholm et al, 2007); maritime pine in Les Landes, France (Lamaud et al, 1994); douglas fir in Northern Holland (Gallagher et al, 1997); spruce in Germany, at Solling (Bleyl, 2001) and near Münchberg (Held and Klemm, 2006); beech in Soro, Denmark (Pryor, 2006); and Amazonian rain forest near Manaus, Brazil (Ahlm et al, 2010). The majority of these studies measured aerosol fluxes using the eddy covariance (EC) technique with Condensational Particle Counters (CPCs), which measure the total particle number concentration over a particle size range typically between 10 nm and 1 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements conducted over grass by Wesely et al (1977), Neumann and den Hartog (1985), Allen et al (1991), Nemitz et al (2002), and Vong et al (2004) were used to evaluate the performance of the five parameterizations. For coniferous forest, modeled deposition velocities were compared with measurements from Lamaud et al (1994), Wyzers and Duyzer (1996), Gallagher et al (1997), Ruijgrok et al (1997), Buzorius et al (2000), Rannik et al (2000), Gaman et al (2004), Pryor et al (2007), and Grönholm et al (2009). Experiments conducted over deciduous forest are limited, and only three studies (Wesely et al, 1983;Pryor, 2006;Matsuda et al, 2010) were used in the present paper.…”
Section: An Evaluation Of the Dry Deposition Parameterizationsmentioning
confidence: 99%
“…Nine studies conducted on coniferous forest (Lamaud et al, 1994;Wyers and Duyzers, 1997;Gallagher et al, 1997;Ruijgrok et al, 1997;Rannik et al, 2000;Buzorious et al, 2000;Gaman et al, 2004;Pryor et al, 2007;and Grönholm et al, 2009) were used to evaluate the accuracy of the parameterizations. In these studies, the largest variations (ranges are given in the parentheses) were associated with u * (0.06-1.30 m s −1 ), U (0.60-6.19 m s −1 ), LAI (6-10 m 2 m −2 ), and d p (0.01-0.60 µm).…”
Section: Evaluation Of Dry Deposition To Coniferous Forestmentioning
confidence: 99%